Estimating Returns to College Attainment: Comparing Survey and State Administrative Data–Based Estimates. (October 2019) - Scott-Clayton, Judith; Wen, Qiao
Background: The increasing availability of massive administrative data sets linking postsecondary enrollees with postcollege earnings records has stimulated a wealth of new research on the returns to college and has accelerated state and federal efforts to hold institutions accountable for students' labor market outcomes. Many of these new research and policy efforts rely on state databases limited to postsecondary enrollees who work in the same state postcollege, with limited information regarding family background and precollege ability. Objectives: In this article, we use recent waves of data from the National Longitudinal Survey of Youth 1997 to provide new, nationally representative, nonexperimental estimates of the returns to degrees, as well as to assess the possible limitations of single-state, administrative data–based estimates. Research design: To do this, we explore the sensitivity of estimated returns to college, by testing different sample restrictions, inclusion of different sets of covariates, and alternative ways of treating out-of-state earnings to approximate the real-world limitations of state administrative databases. Results: We find that failure to control for measures of student ability leads to upward bias, while limiting the sample to college enrollees only leads to an understatement of degree returns. On net, these two biases roughly balance out, suggesting that administrative data–based estimates may reasonably approximate true returns. Conclusions: We conclude with a discussion of the relative advantages and disadvantages of survey versus administrative data for estimating returns to college as well as implications for research and policy efforts based upon single-state administrative databases.